PENGARUH KEMAMPUAN MANAJERIAL KEPALA MADRASAH TERHADAP PROFESIONALITAS GURU DI MTsN 4 ACEH BARAT DAYA - Jihad, Afdhal (Berajah Journal, 2025)
The implementation of teacher development at MTsN 4 Aceh Barat Daya has not been implemented optimally so that teacher professionalism cannot be fully achieved. The aim of this research is to determine the managerial abilities of madrasah heads on teacher professionalism and the influence of the managerial abilities of madrasah heads on teacher professionalism at MTsN 4 Aceh Barat Daya. This type of quantitative research with a sample of 32 people. Data collection techniques used were interviews, questionnaires and documentation. The research results show; 1) The managerial ability of the madrasa head regarding teacher professionalism at MTsN 4 Aceh Barat Daya can be categorized as still not good. As many as 24 people out of 32 respondents ranging in percentage from 61-80% thought that the managerial abilities of madrasa heads in the category were still "Less Optimal", namely 75%. 2) The influence of the madrasa head's managerial ability on the professionalism of teachers at MTsN 4 Aceh Barat Daya shows that teacher performance is in the good category although not optimal. From the descriptive results, it can be seen that the teacher's professionalism score consisting of planning learning, implementing learning and evaluating learning is in the "Good" category but cannot be said to be optimal. Which ranges from 61-80%, namely 56.25%, which means there is a positive influence between the ability of the madrasa head and the professionalism of teachers at MTsN 4 Aceh Barat Daya.